Metal doping effects on PMS activation in FeNCN: Ca-regulated Fe2+/Fe3+ redox behavior for bisphenol A degradation - Muhammad Zain Amjid; Lingzhi He; Amna Zafar; Sabiqa Inam; Zhuwei Liao; Zhuqi Chen (Journal of Environmental Chemical Engineering, 2026)

Nanopesticides in sustainable agriculture: multi-pathogen control, environmental impact, and intelligent delivery systems - Muhammad Abu Bakar Saddique; Yitao Xi; Munazzah Ijaz; Sawera Akram; Shihang Wang; Zhiwei Zhang; Xinyi Yang; Rana Zain Abbas; Maozhi Ren; Xiumei Luo (Bioresource Technology, 2026)

Assessment of growth and physiological effects of dietary Arthrospira platensis in broiler chickens - Zain Ul Abideen; Muhammad Zeshan Haider; Muhammad Kashif Zaman; Muhammad Farooq; Amin F. Majdalawieh; Imad A. Abu-Yousef; Tahira Ruby; Aleem Ahmed Khan (Livestock Science, 2026)

Pigmented cereals as functional food systems: Linking Phytochemistry, processing, and health - Muhammad Bilal; Zain Ul Abideen; Nabila Murtaza; Beenish Abbas; Hafeesa Rasheed; Muhammad Shahar Yar; Mohamed Fawzy Ramadan; Muhammad Hussain Ghazali (Food Chemistry, 2026)

Stepwise activation of peroxymonosulfate by manganese single-atom catalyst for organic pollutant degradation: mediated electron transfer and delayed singlet oxygen generation - Muhammad Zain Amjid; Lingzhi He; Sabiqa Inam; Zhuqi Chen (Chemical Engineering Journal, 2026)

Vitamin B12 and pregabalin combination restored brain waves dynamics and behavior in chronic unpredictable mild stress (CUMS) model of depression - Zain Raza; Muhammad Hussain Ali; Zohabia Rehman; Waseem Ashraf; Fakhir Hannan; Imran Imran; Faleh Alqahtani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

Ethnobotany of desert medicinal plants and their sustainable ethnomedicinal utilization - Salman Majeed; Muhammad Zafar; Sayyara Ibadullayeva; Nahaa M Alotaibi; Sheikh Zain Ul Abidin; Muhammad Rizwan Khan; Sumreen Dawood; Khuzin Dinislam; Adnan Amin (The Science of Nature, 2026)

Biopesticidal activity of callus extracts of Psoralea corylifolia L. on Phenacoccus solenopsis under laboratory conditions - Sarah Ali; Saboohi Raza; Muhammad Abdul Haq; Beena Siddiqua; Syed Muhammad Zain Hashmi (International Journal of Tropical Insect Science, 2026)

Influence of Planting Depth Combined with ZnSO₄ and FeSO₄ on Yield and Starch Quality of Six Potato Cultivars - Harrem Khalid; Muhammad Shafiq; Muhammad Rizwan Tariq; Zain Mushtaq; Maryam Saeed (Potato Research, 2026)

Catboost regressor for monsoon rainfall forecasting in Malaysia using atmospheric Beryllium-7 concentration - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Mohd Zaid Hassan Abdul Rahman; Nur Fatini Abdul Ghani; Muhammad Rawi Mohamed Zain (Modeling Earth Systems and Environment, 2026)

Role of rituximab in treatment of patients with primary central nervous system lymphoma: An updated systematic review and meta-analysis - Kumail Mustafa Ali; Muhammad Farhan Ashraf; Zain Ul Abideen; Armish Rehman; Rumman Javed; Ayena Ghulam Mujtaba; Touba Diwan; Ukasha Khalid; Laiba Ikram (Acta Neurologica Belgica, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Wheat biomass estimation by fusing color index and canopy volume based on UAV RGB images - Zhaosheng Yao; Dongwei Han; Ruimin Shao; Hainie Zha; Shaolong Zhu; Jianliang Wang; Muhammad Zain; Tao Liu; Fei Wu; Yuanzhi Wang; Chengming Sun (Precision Agriculture, 2026)

Unraveling Potato Genotypic Variation Under Smog Stress: A Multi-Trait Study in Central Punjab - Muhammad Daniyal Junaid; Zain Mushtaq; Anum Nazir; Khairiah Mubarak Alwutayd (Potato Research, 2026)

Morpho-molecular diversity and host range dynamics of squash powdery mildew pathogens prevailing in Pothwar Plateau, Pakistan - Beenish Gul; Farah Naz; Mathews L. Paret; Fanny Iriarte; Zain Haider; Gulshan Irshad; Muhammad Azam Khan (Journal of Plant Pathology, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Sustainable cementless concrete reinforced with recycled steel fibers for spun-cast precast pipes: an innovative solution - Safeer Abbas; Moncef Nehdi; Ali Ahmed; Muhammad Abdullah Khan; Muhammad Mubashir Ajmal; Ammad Amir; Muhammad Zain Kashif; Qura tul Ain (Innovative Infrastructure Solutions, 2025)

Estimation of wheat LAI in different leaf layers through LiDAR canopy vertical light distribution parameters and UAV vegetation indices - Dongwei Han; Shaolong Zhu; Muhammad Zain; Weijun Zhang; Guanshuo Yang; Lili Zhang; Binqian Sun; Yuanyuan Zhao; Zhaosheng Yao; Tao Liu; Chengming Sun (Agricultural and Forest Meteorology, 2025)

Impact of COVID-19 on the prevalence of multi-drug-resistant bacteria: a literature review and meta-analysis - Haseeb Ahmed; Zain Ul Abideen; Ammar Azmat; Muhammad Irfan; Salman Anjum; Afaf Dirie (Antonie van Leeuwenhoek, 2025)

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

ODP: A novel indicator for estimating photosynthetic capacity and yield of maize through UAV hyperspectral images - Shaolong Zhu; Tianle Yang; Dongwei Han; Weijun Zhang; Muhammad Zain; Qiaoqiao Yu; Yuanyuan Zhao; Fei Wu; Zhaosheng Yao; Tao Liu; Chengming Sun (Computers and Electronics in Agriculture, 2025)

Green and cost-effective photocatalytic degradation of murexide dye with acid catalyst - Zain Ul Abidin; Adnan Majeed; Muhammad Adnan Iqbal; Muhammad Kashif; Tabinda Fatima; Muhammad Yousif; Muhammad Arbaz; Syed Arslan Hussain; Muhammad Sajid (Clean Technologies and Environmental Policy, 2025)

Influence of Aloe Vera Gel and Neem Extract Application on Postharvest Quality and Shelf Life of Prunus persica - Muhammad Talha; Moazzam Anees; Mubeen Sarwar; M. Rizwan Tariq; Zain Mushtaq; Abdulrahman Alasmari; Anum Nazir; Nazir Ahmad (Applied Fruit Science, 2025)

Assessing future water scarcity in China under climate and socioeconomic change: Can inter-basin transfers mitigate rising stress? - Muhammad Bilal Idrees; Haixing Liu; Siao Sun; Xian Zhou; Muhammad Zain Bin Riaz (Science of The Total Environment, 2025)

Microbial Biofortification of Iron in Solanum tuberosum L. through Siderophore-Producing Rhizobacteria along with L-Tryptophan and Iron Sulphate Supply - Zain Mushtaq; Mehwish Liaquat; Sarvet Jehan; Muhammad Tahir Akram; Muhammad Tauseef Jaffar; Abdulrahman Alasmari (Potato Research, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

Digital twins: cornerstone to circular economy and sustainability goals - Zain Anwar Ali; Mahreen Zain; Raza Hasan; Muhammad Salman Pathan; Hussain AlSalman; Faisal Abdulaziz Almisned (Environment, Development and Sustainability, 2025)
Accurate information is a prerequisite for circulation and greater longevity of materials and products, enabling the economically and environmentally successful transition of circular economy (CE) in the aspiration towards sustainable development. However, a lack of appropriate digital tools is noticed in supplying relevant information and supporting recyclability, reusability, and reducibility processes. This study focuses on a building block of evolving technologies anointed the digital twin (DT). It aims to conceptualize DT as a cornerstone for the CE paradigm, positively influencing sustainability. It also endeavors to scrutinize remarkable implementations of DT-driven CE, accomplishing sustainable development goals (SDGs) in Ireland. An iterative methodology based on four steps is adopted to review an explosion of relevant, recent literature published in 2019–2024 and multiple case studies of Irish construction and manufacturing sectors. By analyzing the literature, this study discovers the evolution and taxonomy of DT, other technologies essential for its deployment, its proactive role in implementing CE and SDGs, and some challenges. Key findings of case studies reveal the current trajectory of employing DT with other digital products, upholding the CE practices within the bounds of the SDGs in Irish companies. In conclusion, DT is a conceivable means for advancing CE solutions and attaining SDGs towards social, economic, and environmental sustainability. The implications of this study are both theoretically and practically significant, encouraging industrialists and academia to adopt DT. It will help scholars gain a thorough understanding and guide industrialists to downsize their carbon footprint and waste, accomplishing SDGs. It will inspire managers with DT-driven information for decision-making and facilitate government and policymakers to collaborate in designing essential policies. Graphical Abstract

HIV mortality trends among the United States population, from 1999–2023: a CDC wonder database study - Abuoma Cherry Ekpendu; Muhammad Sohaib Asghar; Afsana Ansari Shaik; Muhammad Zain Khalid; Maria Duharte; Luis Duharte-Vidaurre; Moustafa Hegazi; Chad K. Brands (Infectious Diseases, 2025)

Application of multiple machine learning algorithms for intelligent prediction of the strength of fine-grained natural soils - Muhammad Shahroz Khalid; Zia ur Rehman; Badee Alshameri; Zain Maqsood; Fazal Hussain; Muhammad Irslan Khalid; Syed Jamal Arbi; Abbas Haider (Arabian Journal of Geosciences, 2025)

Physiological and molecular evidence for phycobilisome degradation in maintaining carbon and nitrogen balance of cyanobacteria - Zhen Luo; Shuangqing Li; Muhammad Zain Ul Arifeen; Fei‑xue Fu; Huayang Gao; Taoran Sun; Lingmei Liu; Xumei Sun; Xinwei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2025)
Phycobilisomes (PBS), the primary light-harvesting complexes in cyanobacteria, are degraded under nitrogen starvation to provide nitrogen for cell growth. This study reveals that carbon supply is a critical prerequisite for PBS degradation under nitrogen deficiency in Synechococcus sp. PCC 7002. Even under nitrogen-deficient conditions, PBS degradation is inhibited in the absence of sufficient carbon. We demonstrate that both the nblAB -mediated PBS-degradation pathway and the ccmLMNK operon-mediated CO 2 -concentrating mechanism are essential for PBS degradation. Furthermore, our findings highlight the critical role of PBS degradation in cyanobacterial adaptation to high C/N conditions. Mutant strains (Mut- nblA and Mut- nblB) deficient in PBS degradation exhibited impaired adaptation to high C/N conditions, as evidenced by their inability to thrive in high NaHCO 3 (nitrogen-free) or CO 2 (low-nitrogen) environments. While these mutants displayed a greener phenotype under high C/N conditions compared to the wild type, they exhibited extensive cellular damage, and significant downregulation of photosynthesis-related genes. These results provide novel insights into the carbon-dependent regulation of PBS degradation and its essential role in cyanobacterial C/N balance, highlighting its significance for their adaptation to fluctuating environmental conditions.

Immunoprotective potential of egg yolk antibodies (IgYs) in controlling necrotic enteritis in broiler chickens - Zain Ul Abadeen; Muhammad Tariq Javed; Tariq Jamil; Syed Muhammad Faizan (Veterinary Immunology and Immunopathology, 2025)

Late Eocene to Pliocene magmatic evolution and its association with gold mineralization in central western Sulawesi, Indonesia - Renaldi Suhendra; Andrea Agangi; Ryohei Takahashi; Marlina A. Elburg; Muhammad Zain Tuakia; Hartaja Wicaksono; Hinako Sato; Iwan Setiawan (Journal of Asian Earth Sciences, 2025)

A comprehensive pyrolysis-gas chromatography/mass spectrometry analysis for the assessment of microplastics in various salts - Jihye Kwon; Hyein Kim; Muhammad Zain Siddiqui; Hui-Seung Kang; Jong-Hyun Choi; Shogo Kumagai; Atsushi Watanabe; Norio Teramae; Eilhann E. Kwon; Young-Min Kim (Food Chemistry, 2025)

Chitosan Induced Modification in Morpho-Physiological, Biochemical and Yield Attributes of Pea (Pisum Sativum L.) Under Salt Stress - Sumreen Anjum; Qurat-ul Ain; Mubeen Sarwar; Muhammad Waqar Alam; Zain Mushtaq; Adnan Mukhtar; M. Irfan Ashraf; Abdulrahman Alasmari (Journal of Soil Science and Plant Nutrition, 2025)

A review of recent advances in green and sustainable technologies for removing 4-nitrophenol from the water and wastewater - Hamza Badamasi; Zain Naeem; Giorgio Antoniolli; Avvaru Praveen Kumar; Abdul Ademola Olaleye; Ismail Shina Sadiq; Naseer Inuwa Durimin-iya; Muhammad Salman Khan (Sustainable Chemistry and Pharmacy, 2025)

Assessing the combined impacts of microplastics and nickel oxide nanomaterials on soybean growth and nitrogen fixation potential - Imran Azeem; Quanlong Wang; Muhammad Adeel; Noman Shakoor; Muhammad Zain; Adnan Anwar khan; Yuanbo Li; Kamran Azeem; Muhammad Nadeem; Guikai Zhu; Rui Yukui (Journal of Hazardous Materials, 2024)

Machine learning integration with response surface methodology to enhance the removal efficacy of arsenate (V) through sulfur-functionalized mxene coated QPPO/PVA AEM - Nimra Saher Zain; Ibrahim A. Shaaban; Farhan Zafar; Hafiz Muhammad Asif; Muhammad Tariq; Muhammad Ali Khan; Naeem Akhtar; Hafsa Kainat; Mohammad A. Assiri (Journal of Environmental Management, 2024)

Viola stocksii: A rich source of antioxidant and anti-inflammatory flavonoid glycosides with converged therapeutic potential against SARS-CoV-2 MPro, spike trimer, and surface glycoproteins - Roshan Zamir; Shanza Munir; Humaira Yasmeen Gondal; Muhammad Nisar; Sami A. Al-Hussain; Ahmed Abbaskhan; Zain M. Cheema; Magdi E.A. Zaki; M. Iqbal Choudhary (Food Bioscience, 2024)

Advancements in sustainable production of biofuel by microalgae: Recent insights and future directions - Muhammad Abdullah; Zain Ali; Muhammad Talha Yasin; Kinza Amanat; Fatima Sarwar; Jallat Khan; Khurshid Ahmad (Environmental Research, 2024)

Combining 2D image and point cloud deep learning to predict wheat above ground biomass - Shaolong Zhu; Weijun Zhang; Tianle Yang; Fei Wu; Yihan Jiang; Guanshuo Yang; Muhammad Zain; Yuanyuan Zhao; Zhaosheng Yao; Tao Liu; Chengming Sun (Precision Agriculture, 2024)

Alteration of the gut microbial composition of critically endangered Malayan tigers (Panthera tigris jacksoni) in captivity during enrichment phase - Mohamad Khairulmunir; Millawati Gani; Abd Rahman Mohd-Ridwan; Kayal Vizi Karuppannan; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Molecular Biology Reports, 2024)

Profusion of microplastics in dental healthcare units; morphological, polymer, and seasonal trends with hazardous consequences for humans - Naseem Akhtar; Arifa Tahir; Abdul Qadir; Rehana Masood; Zain Gulzar; Muhammad Arshad (Journal of Hazardous Materials, 2024)

Achieving wheat seedling freezing injury assessment during the seedling stage using Unmanned Ground Vehicle (UGV) and hyperspectral imaging technology - Zhaosheng Yao; Ruimin Shao; Muhammad Zain; Yuanyuan Zhao; Ting Tian; Jianliang Wang; Dingshun Zhang; Tao Liu; Xiaoxin Song; Chengming Sun (European Journal of Agronomy, 2024)

Aflatoxin B1-associated oxidative stress along with toxicopathological and immunological alterations is efficiently counteracted by dietary supplementation of distillery yeast sludge in broilers - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Muhammad Kashif Saleemi; Halis Oguz; Shafia Tehseen Gul; Rao Zahid Abbas; Ashiq Ali; Sheraz Ahmad Bhatti (Mycotoxin Research, 2024)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Using citizen science data to uncover the invasion of the non-native fish, Hemibagrus wyckioides (Fang and Chaux, 1949) in Peninsular Malaysia - Mohamad Aqmal-Naser; Intan-Faraha A. Ghani; Muhammad Rasul Abdullah Halim; Muhammad Fahmi-Ahmad; Md. Zain Khaironizam; Mohammad Noor Azmai Amal; Zahar Azuar Zakaria; Mohd Lokman Ilham-Norhakim; Amirrudin B. Ahmad (Biological Invasions, 2024)

A comprehensive review of plant-based mucilages as promising candidates for water remediation - Sehar Javed; Zarfishan Zulfiqar; Zain Fatima; Gulzar Muhammad; Muhammad Ajaz Hussain; Muhammad Mushtaq; Muhammad Tahir Haseeb (Journal of Environmental Chemical Engineering, 2024)

Exposure Levels, Health Risks, Spatially Distribution, Multivariate Statistics and Positive Matrix Factorization Model of Heavy Metals from Wild solid Waste Dumpsites - Predrag Ilić; Svetlana Ilić; Abdur Rashid; Zain Mushtaq; Sanja Mrazovac Kurilić; Ljiljana Stojanović Bjelić; Dragana Nešković Markić; Zia Ur Rahman Farooqi; Muhammad Yousuf Jat Baloch; Tariq Mehmood; Zahid Ullah; Sobia Riaz (Water, Air, & Soil Pollution, 2024)

APW: An ensemble model for efficient wheat spike counting in unmanned aerial vehicle images - Zhaosheng Yao; Dingshun Zhang; Ting Tian; Muhammad Zain; Weijun Zhang; Tianle Yang; Xiaoxin Song; Shaolong Zhu; Tao Liu; Haijiao Ma; Chengming Sun (Computers and Electronics in Agriculture, 2024)

Biofortification of Iron in Potato Through Rhizobacteria and Plant Growth Regulator - Zain Mushtaq; Ibrahim Al-Ashkar; Muhammad Habib-ur-Rahman; Ayman El Sabagh; Predrag Ilić (Potato Research, 2024)

Integrative taxonomy of the featherback fish genus Chitala (Osteoglossomorpha: Notopteridae) in Peninsular Malaysia - Luqman Hakim Ruzman; Jamsari Amirul Firdaus Jamaluddin; Abdullah Halim Muhammad‐Rasul; Tedjo Sukmono; Md. Zain Khaironizam; Sébastien Lavoué (Zoologica Scripta, 2024)
The taxonomy of the freshwater featherback fish genus Chitala (Osteoglossomorpha: Notopteridae) remains unsettled because delimiting and naming Chitala species based solely on morphology led to different hypotheses. In this study, we aim to determine the number and identity of Chitala species present in Peninsular Malaysia by employing an integrative taxonomic approach that combines morphology and two mitochondrial markers: the cytochrome c oxidase subunit I (COI) and cytochrome b genes. A total of 60 specimens of Chitala were collected throughout Peninsular Malaysia. Initially, all specimens were sorted into three distinct categories based on their body marking patterns. A molecular phylogenetic analysis revealed that each of these groups was monophyletic, and an automated species partition method further recognized them as distinct species. These results support the presence of three Chitala species in Peninsular Malaysia, even though a multivariate morphometric analysis failed to fully differentiate each of these three species. Comparison with original species descriptions and genetic data from an additional 70 Chitala specimens from neighbouring regions allowed us to name these species as Chitala lopis , Chitala borneensis , and Chitala ornata . We also showed the presence of two undescribed species in Indonesia.

Deep eutectic solvents as sustainable extraction media for extraction of polysaccharides from natural sources: Status, challenges and prospects - Noorfatimah Yahaya; Ahmad Husaini Mohamed; Muhammad Sajid; Nur Nadhirah Mohamad Zain; Pao-Chi Liao; Kit Wayne Chew (Carbohydrate Polymers, 2024)

Sugarcane bagasse biochar boosts maize growth and yield in salt-affected soil by improving soil enzymatic activities - Muhammad Tauseef Jaffar; Wenqian Chang; Jianguo Zhang; Ahmed Mukhtar; Zain Mushtaq; Muhammad Ahmed; Zahir Ahmad Zahir; Kadambot H.M. Siddique (Journal of Environmental Management, 2024)

Green synthesis, properties, and biomedical potential of gold nanoparticles: A comprehensive review - Zain Fatima; Ramsha Saleem; Rana Rashad Mahmood Khan; Maira Liaqat; Muhammad Pervaiz; Zohaib Saeed; Gulzar Muhammad; Muhammad Amin; Shahzad Rasheed (Biocatalysis and Agricultural Biotechnology, 2024)

Activation of persulfate, peroxymonosulfate, and peroxydisulfate using metal-organic framework catalysts for degradation of antibiotics: Identification, quantification, interconversion, and transformation of reactive species - Irfan Ijaz; Aysha Bukhari; Attia Shaheen; Ammara Nazir; Ezaz Gilani; Hina Zain; Shabbir Muhammad; Sajjad Hussain (Journal of Environmental Chemical Engineering, 2024)

Two-dimensional MXenes: A route from synthesis to applications in self-powered IoT devices - Muhammad Ahsan Saeed; Muhammad Zain Qamar; Zubair Khalid; Elham Chamanehpour; Yogendra Kumar Mishra (Chemical Engineering Journal, 2024)

Drought stress in sorghum: physiological tools, breeding technology, Omics approaches and Genomic-assisted breeding -A review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Zain Ali; Muhammad Owais Khan (Journal of Soil Science and Plant Nutrition, 2024)

Poly-(ionic liquid) coated with magnetic nanoparticles for micro solid phase extraction of polycyclic aromatic hydrocarbons in food samples - Faizah Muhammad Yunus; Yatimah Alias; Noorfatimah Yahya; Nur Nadhirah Mohamad Zain; Muggundha Raoov (Food Additives & Contaminants: Part A, 2024)

Cryptic footprint of thallium in soil-plant systems; A review - Noman Shakoor; Samama Tariq; Muhammad Adeel; Imran Azeem; Muhammad Nadeem; Muhammad Zain; Yuanbo Li; Wang Quanlong; Rabia Aslam; Yukui Rui (Chemosphere, 2024)

Retraction Note: The non-linear relationship between carbon dioxide emissions, financial development and energy consumption in developing European and Central Asian economies - Leng Chunyu; Syed Zain-ul-Abidin; Wajeeha Majeed; Syed Muhammad Faraz Raza; Ishtiaq Ahmad (Environmental Science and Pollution Research, 2024)

Organic waste-to-bioplastics: Conversion with eco-friendly technologies and approaches for sustainable environment - Zain Ali; Muhammad Abdullah; Muhammad Talha Yasin; Kinza Amanat; Khurshid Ahmad; Ishfaq Ahmed; Muther Mansoor Qaisrani; Jallat Khan (Environmental Research, 2024)

Scorpion sting in Hafizabad, Pakistan: Facility based epidemiological study - Muhammad Mohsin Ahsan; Zoya Gulzar; Hafiz Muhammad Tahir; Aamir Ali; Muhammad Ismail; Muhammad Khalid Mukhtar; Zain Ul Abdin (Toxicon, 2024)

Global insights into micro-macro mechanisms and environmental implications of limestone calcined clay cement (LC3) for sustainable construction applications - Nauman Ijaz; Wei-Min Ye; Zia ur Rehman; Zain Ijaz; Muhammad Faisal Junaid (Science of The Total Environment, 2024)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Bacterial inoculation remediates heavy metals toxicity through modulating biochemicals and antioxidant enzymes of Daucus carota L. grown in lead contaminated soil - Naima Huma Naveed; Naveed Abbas Nasir; Anis Ali Shah; Tahir Shahzad; Nasim Ahmad Yasin; Zain Ali; Muhammad Jamil; Talha Javed; Aamir Ali (South African Journal of Botany, 2023)

Lithium-induced alterations in soybean nodulation and nitrogen fixation through multifunctional mechanisms - Noman Shakoor; Muzammil Hussain; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Peng Zhang; Yuanbo Li; Wang Quanlong; Robert Horton; Yukui Rui (Science of The Total Environment, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Pseudomonas fluorescens and L-tryptophan application triggered the phytoremediation potential of sunflower (Heliantus annuus L.) in lead-contaminated soil - Muhammad Tauseef Jaffar; Zain Mushtaq; Abdul Waheed; Hafiz Naeem Asghar; Jianguo Zhang; Jiale Han (Environmental Science and Pollution Research, 2023)

Development of high resolution daily gridded precipitation and temperature dataset for potohar plateau of indus basin - Muhammad Wasif Khan; Shakil Ahmad; Zakir Hussain Dahri; Zain Syed; Khalil Ahmad; Firdos Khan; Muhammad Azmat (Theoretical and Applied Climatology, 2023)

Geospatial modeling of heterogeneous geotechnical data using conventional and enhanced conception of modified Shepard method-based IDW algorithms: application and appraisal - Zain Ijaz; Cheng Zhao; Nauman Ijaz; Zia ur Rehman; Aashan Ijaz; Muhammad Faisal Junaid (Bulletin of Engineering Geology and the Environment, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Simultaneous removal of Norfloxacin, Ciprofloxacin, and copper from aqueous solution by chitosan and MXene functionalized graphene oxide ternary composite based on anion-synergistic interaction - Aysha Bukhari; Irfan Ijaz; Ezaz Gilani; Ammara Nazir; Hina Zain; Shabbir Muhammad; Awais Bukhari; Attia shaheen; Sajjad Hussain (Chemical Engineering Journal, 2023)

Barriers to the adoption of social welfare measures in the electricity tariff structure of developing countries: A case of Pakistan - Muhammad Zain Jan; Kafait Ullah; Faisal Abbas; Hassan Abdullah Khalid; Tariq M. Bajwa (Energy Policy, 2023)

Editorial: Occurrence, migration and degradation of emerging organic pollutants in the estuarine environment - Qing Luo; Muhammad Adeel; Muhammad Arslan Ahmad; Guangzhe Jin; Muhammad Zain (Frontiers in Marine Science, 2023)

Investigation of resource curse hypothesis: the role of renewable energy and urbanization in realizing environmental sustainability in China - Yongming Huang; Syed Zain Ul Abidin; Syed Muhammad Faraz Raza (Environmental Science and Pollution Research, 2023)

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

Remediation methods of heavy metal contaminated soils from environmental and geotechnical standpoints - Zia ur Rehman; Muhammad Faisal Junaid; Nauman Ijaz; Usama Khalid; Zain Ijaz (Science of The Total Environment, 2023)

Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives - Noman Shakoor; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Aown Abbas; Muzammil Hussain; Yaqi Jiang; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Chemosphere, 2023)

Role of agricultural resource sector in environmental emissions and its explicit relationship with sustainable development: Evidence from agri-food system in China - Muddassar Sarfraz; Kashif Iqbal; Yichu Wang; Muhammad Shoaib Bhutta; Zain ul Abidin Jaffri (Resources Policy, 2023)

Environment relevant concentrations of lithium influence soybean development via metabolic reprogramming - Noman Shakoor; Muhammad Adeel; Muhammad Arslan Ahmad; Muzammil Hussain; Imran Azeem; Muhammad Zain; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Journal of Hazardous Materials, 2023)

Renewable energy production from novel and non-edible seed oil of Cordia dichotoma using nickel oxide nano catalyst - Rozina; Mushtaq Ahmad; Nasib Qureshi; Muhammad Zafar; Sher Aman Ullah; Sheikh Zain Ul Abidin (Fuel, 2023)

Pharmacological potential of Sargassum sp. of west coast of Maharashtra Kunkeshwar, India - Gholamreza Abdi; Vanita Chandrashekhar Karande; Arifullah Mohammed; Maryam Abbasi Tarighat; Khang Wen Goh; Zulhisyam Abdul Kari; Lee Seong Wei; Muhammad Rajaei Ahmad Mohd Zain; Mehdi Mohammadi; Gaik Ee Lee; Mukul M. Barwant (Frontiers in Marine Science, 2022)
A promising plant group that is important in medicine is the seaweed. In this investigation, we have focused on the pharmacological prospects of brown algae ( Sargassum sp ). Nutraceuticals refer to products that may combine pharmacological and nutrition. We have collected the plant material close to Kunkeeshwar in Sindhudurg, Maharashtra’s western coast. We focused on the Physicochemical Attributes of Sargassum sp., and the study found that the ash value (41 ± 0.67), moisture content (1.33 ± 0.038), alcohol-soluble extractive value (1.5 ± 0.030), moisture content (1.33 ± 0.038), and total cash value (41 ± 0.67) are all stated in (%).The GCMS findings, which demonstrate that a total of 25 chemicals were discovered in the aqueous extract of Sargassum sp., also represent their nutritional profile. All of these substances have chromatograms that can be observed.1-Hexyl-2-nitrocyclohexane is the substance with the second-largest retention duration and relative areas, followed by n-hexadanoic acid. The presence of ocladecanoic acid was later determined. The explanation for how the activity is concentration-dependent is pharmacological activity, particularly antioxidant activity as shown by the DPPH assay.2μg/mL is -1545.4 ± 0.05. as a minimum. and at (32 g/mL is 7.67 ± 0.05) is the highest. The antifungal activity of Candida albicans (12.8 mm) and Aspergillus niger (14.4 mm) both exhibit zone inhibition when tested against two distinct pathogen however, the antibacterial activity of three different bacteria demonstrates that Staphylococcus aureus (12 mm), Bacillus subtilis (10 mm), Proteus mirabilis (12.8 mm), and Escherichia. coli are all zone inhibited (13mm). Brown algae offer the greatest potential for human health nutrition, while pharmacological analysis is helpful for therapeutic application, according to the overall analysis.

Strengthening potential of xanthan gum biopolymer in stabilizing weak subgrade soil - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Zain Ijaz; Zia ur Rehman (Clean Technologies and Environmental Policy, 2022)

Acceleration of flow modeling using a freeware 2D GPU-shallow water equations code - Prince Mahmood; Sajjad Haider; Hamza Farooq Gabriel; Muhammad Shahid; Zain Syed (Arabian Journal of Geosciences, 2022)

Water quality and health risk assessment of trace elements in surface water at Punjnad Headworks, Punjab, Pakistan - Saima Naz; Borhan Mansouri; Ahmad Manan Mustafa Chatha; Qudrat Ullah; Zain Ul Abadeen; Muhammad Zahoor Khan; Adnan Khan; Saba Saeed; Rayees Ahmad Bhat (Environmental Science and Pollution Research, 2022)

Combined efficacy of Cinnamomum zeylanicum and doxorubicin against leukemia through regulation of TRAIL and NF-kappa B pathways in rat model - Sidra Bukhari; Muhammad Hamid Siddique; Anum Naeem; InamUllah Khan; Zain Ali; Asiya Essa; Falak Fazal; Riffat Aysha Anis; Lukas Moran; Aneesa Sultan; Iram Murtaza; Petr Vanhara; et al. (Molecular Biology Reports, 2022)

Correction to: Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2022)

The Interactive Approach of Rhizobacteria and l-tryptophan on Growth, Physiology, Tuber Characteristics, and Iron Concentration of Potato (Solanum tuberosum L.) - Zain Mushtaq; Hafiz Naeem Asghar; Zahir Ahmad Zahir; Muhammad Maqsood (Journal of Plant Growth Regulation, 2022)

ICT, renewable energy, financial development, and CO2 emissions in developing countries of East and South Asia - Zakia Batool; Syed Muhammad Faraz Raza; Sajjad Ali; Syed Zain Ul Abidin (Environmental Science and Pollution Research, 2022)

Recent approaches on the optimization of biomass gasification process parameters for product H2 and syngas ratio: a review - Muhammad Zain Siddiqui; Mahshab Sheraz; Umair Ali Toor; Ali Anus; Abid Mahmood; Muhammad Haseeb; Muhammad Ibrahim; Kuan Shiong Khoo; Vishno Vardhan Devadas; Muhammad Mubashir; Sami Ullah; Pau Loke Show (Environment, Development and Sustainability, 2022)

Greening the workforce in higher educational institutions: The pursuance of environmental performance - Qazi Muhammad Ali; Qasim Ali Nisar; Rana Zain ul Abidin; Rabia Qammar; Kashif Abbass (Environmental Science and Pollution Research, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

RETRACTED ARTICLE: The non-linear relationship between carbon dioxide emissions, financial development and energy consumption in developing European and Central Asian economies - Leng Chunyu; Syed Zain-ul-Abidin; Wajeeha Majeed; Syed Muhammad Faraz Raza; Ishtiaq Ahmad (Environmental Science and Pollution Research, 2021)

Effect of oxygen concentrations and branched‐chain amino acids on the growth and development of sub‐seafloor fungus, Schizophyllum commune 20R‐7‐F01 - Muhammad Zain Ul Arifeen; Zhi‐Jun Ma; Si Wu; Jun‐Zhong Liu; Ya‐Rong Xue; Chang‐Hong Liu (Environmental Microbiology, 2021)
Summary Fungi have been reported to be the dominant eukaryotic group in anoxic sub‐seafloor sediments, but how fungi subsist in the anoxic sub‐marine sedimental environment is rarely understood. Our previous study demonstrated that the fungus, Schizophyllum commune 20R‐7‐F01 isolated from a ~2 km sediment below the seafloor, can grow and produce primordia in the complete absence of oxygen with enhanced production of branched‐chain amino acids (BCAAs), but the primordia cannot be developed into fruit bodies without oxygen. Here, we present the individual and synergistic effects of oxygen and BCAAs on the fruit‐body development of this strain. It was found that the fungus required a minimum oxygen concentration of 0.5% pO 2 to generate primordia and 1% pO 2 to convert primordia into mature fruit body. However, if BCAAs (20 mM) were added to the medium, the primordium could be developed into fruit body at a lower oxygen concentration up to 0.5% pO 2 where genes fst4 and c2h2 playing an important role in compensating oxygen deficiency. Moreover, under hypoxic conditions, the fungus showed an increase in mitochondrial number and initiation of auto‐phagocytosis. These findings suggest that the fruit‐body formation of S. commune may have multiple mechanisms, including energy and amino acid metabolism in response to oxygen concentrations.

Adoption of green banking practices and environmental performance in Pakistan: a demonstration of structural equation modelling - Alam Rehman; Irfan Ullah; Fakhr-e-Alam Afridi; Zain Ullah; Muhammad Zeeshan; Arif Hussain; Haseeb Ur Rahman (Environment, Development and Sustainability, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

In Vitro Studies for the Evaluation of Insecticidal Potential of the Venom of Endoparasitic Wasp Aenasius arizonensis (Girault) (Hymenoptera, Encyrtidae) - Saqi Kosar Abbas; Zain Ul Abdin; Muhammad Arshad; Fiaz Hussain; Amer Jamil (International Journal of Peptide Research and Therapeutics, 2021)

The anaerobic survival mechanism of Schizophyllum commune 20R‐7‐F01 , isolated from deep sediment 2 km below the seafloor - Muhammad Zain Ul Arifeen; Chen Chu; Xinyi Yang; Junzhong Liu; Xin Huang; Yunan Ma; Xuan Liu; Yarong Xue; Changhong Liu (Environmental Microbiology, 2021)
Summary Fungi dominated the eukaryotic group in the anaerobic sedimentary environment below the ocean floor where they play an essential ecological role. However, the adaptive mechanism of fungi to these anaerobic environments is still unclear. Here, we reported the anaerobic adaptive mechanism of Schizophyllum commune 20R‐7‐F01, isolated from deep coal‐bearing sediment down to ~2 km below the seafloor, through biochemical, metabolomic and transcriptome analyses. The fungus grows well, but the morphology changes obviously and the fruit body develops incompletely under complete hypoxia. Compared with aerobic conditions, the fungus has enhanced branched‐chain amino acid biosynthesis and ethanol fermentation under anaerobic conditions, and genes related to these metabolisms have been significantly up‐regulated. Additionally, the fungus shows novel strategies for synthesizing ethanol by utilizing both glycolysis and ethanol fermentation pathways. These findings suggest that the subseafloor fungi may adopt multiple mechanisms to cope with lack of oxygen.

Histomorphology of Seminal Vesicles Subsequent to Exogenous Neurokinin B Administration in New Zealand White Rabbits - Zain Ullah; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

Telomerase reverse transcriptase downregulation by RNA interference modulates endoplasmic reticulum stress and mitochondrial energy production - Muhammad Zuhair Mohd Zain; Nor Hayati Ismail; Nadhirah Ahmad; Sarina Sulong; Saiful Anuar Karsani; Nazia Abdul Majid (Molecular Biology Reports, 2020)

Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2020)

Silicon and Its Application Methods Improve Physiological Traits and Antioxidants in Triticum aestivum (L.) Under Cadmium Stress - Shafeeq-ur-Rahman; Qi Xuebin; Xiao Yatao; Muhammad Irfan Ahmad; Muhammad Shehzad; Muhammad Zain (Journal of Soil Science and Plant Nutrition, 2020)

Re-examining log law velocity profile in smooth open channel flows - Nadeeka S. Miguntanna; Hamish Moses; Muttucumaru Sivakumar; Shu-Qing Yang; Keith James Enever; Muhammad Zain Bin Riaz (Environmental Fluid Mechanics, 2020)

Hydrological appraisal of rainfall estimates from radar, satellite, raingauge and satellite–gauge combination on the Qinhuai River Basin, China - Muhammad Ilyas Abro; Dehua Zhu; Ming Wei; Asghar Ali Majidano; Murad Ali Khaskheli; Zain Ul Abideen; Muhammad Sohail Memon (Hydrological Sciences Journal, 2019)

Comparative effect of mesquite biochar, farmyard manure, and chemical fertilizers on soil fertility and growth of onion (Allium cepa L.) - Mumtaz Khan; Kaneez Fatima; Rehan Ahmad; Rafia Younas; Muhammad Rizwan; Muhammad Azam; Zain ul Abadin; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Biomarkers of pyrethroid toxicity in fish - Sana Ullah; Zhongqiu Li; Amina Zuberi; Muhammad Zain Ul Arifeen; Mirza Muhammad Faran Ashraf Baig (Environmental Chemistry Letters, 2019)

Is Malaysia’s banded langur, Presbytis femoralis femoralis, actually Presbytis neglectus neglectus? Taxonomic revision with new insights on the radiation history of the Presbytis species group in Southeast Asia - Muhammad Abu Bakar Abdul-Latiff; Hanisah Baharuddin; Pazil Abdul-Patah; Badrul Munir Md-Zain (Primates, 2019)

Natural and synthetic estrogens in leafy vegetable and their risk associated to human health - Muhammad Adeel; Muhammad Zain; Shah Fahad; Muhammad Rizwan; Asif Ameen; Hao Yi; Mansoor A. Baluch; Jie Yinn Lee; Yukui Rui (Environmental Science and Pollution Research, 2018)

Correction to: Pre-existing Small Vessel Disease in Patients with Acute Stroke from the Middle East, Southeast Asia, and Philippines - Naveed Akhtar; Abdul Salam; Saadat Kamran; Atlantic D’Souza; Yahia Imam; Pablo Garcia Bermejo; Muhammad Faisal Wadiwala; Ahmed Own; Ahmed ElSotouhy; Surjith Vattoth; Paula Bourke; Zain Bhutta; et al. (Translational Stroke Research, 2018)

Effects of feeding bentonite clay upon ochratoxin A–induced immunosuppression in broiler chicks - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Sheraz Ahmed Bhatti (Food Additives & Contaminants: Part A, 2018)

Functional analysis of the venom of mealybug parasitoid Aenasius bambawalei (Hymenoptera: Encyrtidae) - Saqi Kosar Abbas; Zain ul Abdin; Muhammad Jalal Arif; Amer Jamil (Biologia, 2014)